How the Kenyan runner`s body structure affects sports results - Eksterowicz, J.; Napierala, M.; Zukow, W. (Human Movement, 2016)
Purpose. The aim of this study was to determine the dependency between somatic parameters of selected Kenyan marathon runners and results achieved in long-distance runs (marathon, half-marathon, 10,000 meters). Methods. The research study was conducted on a sample of 9 top-level long-distance Kenyan runners whose results in Poland correspond to International Masterclass. All runners` (mean ± SD) age: 23.67 ± 4.41 years, weight: 55.98 ± 4.84 kg, height: 169.18 cm ± 4.15cm. All participants had their anthropometric measurements taken: length, width, size and sum of three skin-folds. Having taken those anthropometric measurements, Body Mass Index (BMI), Arm Muscle Circumference (AMC), Waist to Hip Ratio (WHR), body mass and body fat (FM) (%), fat free mass (FFM) were calculated using the Durnin-Womersley method. Results and conclusions. Significant relations (significant correlation, important dependency) were observed in dependency between 10,000 meters results and the foot breadth (r = 0.765) and torso length (r = 0.755). Similar relationships occurred between marathon results and the arm length (r = 0.73), forearm length (r = 0.75) and hip width (r = 0.77).